Pengembangan Game Petualang untuk Pembelajaran Berhitung - Indah Rahmawati; Ibut Priono Leksono; Harwanto Harwanto (Universitas Negeri Malang, 2020)
Abstrak: Penelitian ini menghasilkan media pembelajaran berupa game yang diaplikasikan pada perangkat yang memakai sistem android. Selama ini anak-anak menghilangkan kejenuhan dengan game. Oleh karena itu, perlu dikembangkan media pembelajaran berupa game yang bertujuan agar siswa dapat memanfaatkan waktu luang dengan sesuatu yang berguna. Penelitian ini bertujuan untuk menyediakan media pembelajaran game petualang yang telah divalidasi oleh ahli isi, ahli media dan ahli desain sebagai pendukung pembelajaran berhitung. Metode dalam penelitian pengembangan ini menggunakan metode Penelitian dan Pengembangan (P&P). Penelitian ini menghasilkan data berupa game petualang untuk pembelajaran berhitung yang dilengkapi buku petunjuk penggunaan bisa diperoleh di playstore. Validasi ahli isi sebesar 84,76%, validasi ahli media dan desain sebesar 91,82%, Angket respon siswa terhadap game petualang untuk pembelajaran berhitung mencapai kriteria sangat baik. Abstract: This study developed a learning media in the form of games that were applied to devices using the Android system. During this time children eliminate boredom with games. Therefore, learning media in the form of games are developed so that students can take advantage of free time with something useful. This research aims to provide adventurous game learning media that have been validated by material experts, media experts and design expert as a support for numeracy learning. The method in this research use the Research and Development (P&P) method. This study produces form adventurous games for numeracy learning that are equipped with user manuals can be obtained at Playstore, Material expert validation is 84,76%, Media and design expert validation is 91,82%. Questionnaire responses of students to the adventurous game for learning to count reached very good criteria.Abstract: This study produces learning media in the form of games that are applied to devices using the Android system. So far, children get rid of boredom with games. Therefore, it is necessary to develop learning media in the form of games that aim so that students can take advantage of their spare time with something useful. This study aims to provide an adventurous game learning media that has been validated by content experts, media experts and design experts as support for learning to count. The method in this development research uses the Research and Development (P&P) method. This research produces data in the form of an adventurous game for learning arithmetic which is equipped with a user manual which can be found in the playstore. Content expert validation was 84.76%, media and design expert validation was 91.82%, student response questionnaires to adventurous games for learning arithmetic reached very good criteria. This study developed a learning media in the form of games that were applied to devices using the Android system. During this time children eliminate boredom with games. Therefore, learning media in the form of games are developed so that students can take advantage of free time with something useful. This research aims to provide adventurous game learning media that have been validated by material experts, media experts and design experts as a support for numeracy learning. The method in this research use the Research and Development (P&P) method. This study produces a form of adventurous games for numeracy learning that are equipped with user manuals can be obtained at Playstore, Material expert validation is 84.76%, Media and design expert validation is 91.82%. Questionnaire responses of students to the adventurous game for learning to count reached very good criteria.